Effects of Hair Metals on Body Weight in Iranian Children Aged 20 to 36 Months - Mohsen VIGEH; Kazuhito YOKOYAMA; Takehisa MATSUKAWA; Atsuko SHINOHARA; Mamak SHARIAT; Katsumi OHTANI (Tehran University of Medical Sciences, 2017)
Background: Although the level of exposure to many toxic metals decreased recently, the adverse effects of these metals on children's growth and development remain a serious public health issue. Methods: The present study was conducted in three teaching hospitals affiliated with Tehran University of Medical Sciences (Tehran, Iran) from Sep 2012 to Mar 2013. To study the relationship between metals and childhood growth, concentrations of zinc and several potentially toxic metals (lead, cadmium, antimony, cobalt, and molybdenum) were measured in scalp hair for 174 children, aged 20 to 36 months. Results: The hair concentrations of cobalt were significantly (P<0.05) higher in children at the lower percentile of weight than in higher-weight children (0.026 ± 0.04 vs. 0.015 ± 0.01 µg/g, respectively). Hair contents of lead, cobalt, and antimony were significantly higher (P<0.05) in girls than in boys (8.08 ± 8.7 vs. 4.92 ± 5.6 µg/g for lead, 0.026 ± 0.03 vs. 0.16 ± 0.02 µg/g for cobalt, and 0.188 ± 0.29 vs. 0.102 ± 0.12 µg/g for antimony). There were also significant correlations between lead and other metals in the children's hair. Conclusion: Gender may play a significant role in absorption and/or accumulation of metals. It should be considered when we study metal toxicity in children.